Features of Women's Language Used by Kamala Khan in Ms. Marvel TV Series: A Sociolinguistics Study - Shanya Putri Faiziah Pribadi; Eliwarti; Purwanti, Indah Tri (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
This research aimed to identify the women’s language features used by Kamala Khan in the TV series Ms. Marvel (2022) based on the theory of women’s language proposed by Lakoff (1975). It was conducted using the descriptive qualitative method. To collect the data, the researcher watched the TV series several times and noted the utterances Kamala Khan produced that used women’s language features in an observation list. Based on the data collected by the researcher, in all six episodes of the TV series Ms. Marvel (2022), Kamala Khan used women’s language features 180 times in the 971 utterances she produced. The researcher found that 9 out of 10 women’s language features, as described by Lakoff (1975), were used by Kamala Khan in her utterances. Those features are lexical hedges or fillers (65), rising intonation on declaratives (33), “superpolite” forms (29), tag questions (16), avoidance of strong swear words (13), emphatic stress (10), intensifiers (9), “hypercorrect” grammar (3), and “empty” adjectives (3). Lexical hedges or fillers are the most frequent women’s language features used by Kamala Khan in Ms. Marvel (2022). Meanwhile, precise color terms did not occur in any of Kamala Khan’s utterances.